Private Vegas [compact disc, unabridged] - Patterson, James, 1947- (Patterson, James, 1947- Private novels., 2015)
Las Vegas is a city of contradictions: seedy and glamorous, secretive and wild, Vegas attracts people of all kinds--especially those with a secret to hide, or a life to leave behind. It's the perfect location for Lester Olsen's lucrative business. He gets to treat gorgeous, young women to five-star restaurants, splashy shows, and limo rides--and then he teaches them how to kill. Private's Jack Morgan spends most of his time in Los Angeles, where his top investigation firm has its headquarters. But a hunt for two criminals leads him to the city of sin--and to a murder ring that is more seductively threatening than anything he's witnessed before.